นโยบายภาครัฐในการส่งเสริมการประกอบอาชีพคนพิการ : ศึกษากรณีคนพิการทางด้านสายตา - เทวพงษ์ พวงเพชร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This thesis studies the State policy on vocational promotion for disabled people, with a focus on people with visual impairment. The main inquiry is the current state of vocational opportunities among people with disabilities and those with visual disability. The study uses political theories on human rights, income distribution, affirmative action, and street-level bureaucracy as the framework for analysis. The descriptive, qualitative approach is used as the main research method, with a supplement of structured survey of disabled people. Following are the major findings and analyses. The State policy still lacks the efficacy in promoting job opportunities for the disabled people. The policy is rather general, in that it does not pay specific attention to the needs of people with different types of impairments. The Thai people with disabilities, therefore, remain having limited job opportunities and resort to such jobs as lottery vending, further negatively affecting their rights and dignity. Lastly, the research also finds that in practice, both the public and private sectors still manage to limit employment opportunities among people with disabilities and especially those with visual impairment. With the above findings and analyses, this research proposes the necessity in further improving State policy that could affect the rights and dignity of disabled people. More progression in terms of policy enhancement in many aspects of vocational promotion is encouraged, with more attention to people with specific needs due to different types of impairment. Their job skills have to be promoted. As such, it is expected that employers would have less reason to unwelcome people with disabilities.